Draft genome assembly and annotation of Glycyrrhiza uralensis, a medicinal legume. (24th October 2016) - Mochida, Keiichi; Sakurai, Tetsuya; Seki, Hikaru; Yoshida, Takuhiro; Takahagi, Kotaro; Sawai, Satoru; Uchiyama, Hiroshi; Muranaka, Toshiya; Saito, Kazuki
Summary: Chinese liquorice/licorice ( Glycyrrhiza uralensis ) is a leguminous plant species whose roots and rhizomes have been widely used as a herbal medicine and natural sweetener. Whole‐genome sequencing is essential for gene discovery studies and molecular breeding in liquorice. Here, we report a draft assembly of the approximately 379‐Mb whole‐genome sequence of strain 308‐19 of G. uralensis ; this assembly contains 34 445 predicted protein‐coding genes. Comparative analyses suggested well‐conserved genomic components and collinearity of gene loci (synteny) between the genome of liquorice and those of other legumes such as Medicago and chickpea. We observed that three genes involved in isoflavonoid biosynthesis, namely, 2‐hydroxyisoflavanone synthase ( CYP93C ), 2, 7, 4′‐trihydroxyisoflavanone 4′‐ O ‐methyltransferase/isoflavone 4′‐ O ‐methyltransferase ( HI4OMT ) and isoflavone‐7‐ O ‐methyltransferase ( 7‐IOMT ) formed a cluster on the scaffold of the liquorice genome and showed conserved microsynteny with Medicago and chickpea. Based on the liquorice genome annotation, we predicted genes in the P450 and UDP‐dependent glycosyltransferase (UGT) superfamilies, some of which are involved in triterpenoid saponin biosynthesis, and characterised their gene expression with the reference genome sequence. The genome sequencing and its annotations provide an essential resource for liquorice improvement through molecular breeding and the discovery of useful genes for engineering bioactive components through synthetic biology approaches. Significance Statement: Chinese licorice legumes, roots, and rhizomes are used as herbal medicines and natural sweeteners. Here we report the draft genome sequence, which will facilitate identification, isolation, and editing of useful genes to improve agronomic and medicinal traits through molecular breeding.